2020
DOI: 10.4049/jimmunol.1900251
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani Subverts Host Immune Response by Epigenetic Reprogramming of Macrophage M(Lipopolysaccharides + IFN-γ)/M(IL-10) Polarization

Abstract: Reciprocal changes in histone lysine methylation/demethylation of M(LPS + IFN-g)/M(IL-10) genes is one of the factors that direct macrophage polarization and contribute to host defense/susceptibility toward infection. Although, histone lysine methyltransferases and lysine demethylases orchestrate these events, their role remains elusive in visceral leishmaniasis, a disease associated with macrophage M(IL-10) polarization. In this study, we observed that L. donovani induced the expression of histone lysine meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 43 publications
5
32
0
Order By: Relevance
“…Previous studies have demonstrated that in addition to TGF-β/Smad3, other signaling pathways such as STAT3, NF-kB, ERK1/2, and AKT, are activated and involved in cellular events, including survival, proliferation, and inflammation during the course of renal fibrosis. [8][9][10][11][12][34][35][36][37][38] Our current studies showed that SMYD2 inhibition blocked phosphorylation of all these signaling molecules in vivo and in vitro, supporting the importance of these pathways in transducing SMYD2 activation to renal fibrogenesis. The mechanism by which SMYD2 controls phosphorylation and activation of intracellular signaling molecules remains incompletely understood but is being explored.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have demonstrated that in addition to TGF-β/Smad3, other signaling pathways such as STAT3, NF-kB, ERK1/2, and AKT, are activated and involved in cellular events, including survival, proliferation, and inflammation during the course of renal fibrosis. [8][9][10][11][12][34][35][36][37][38] Our current studies showed that SMYD2 inhibition blocked phosphorylation of all these signaling molecules in vivo and in vitro, supporting the importance of these pathways in transducing SMYD2 activation to renal fibrogenesis. The mechanism by which SMYD2 controls phosphorylation and activation of intracellular signaling molecules remains incompletely understood but is being explored.…”
Section: Discussionsupporting
confidence: 71%
“…Understanding of miRNA regulation during parasite infection by high order chromatin elements like SE will add a new dimension to Leishmania infection biology. Parmar et al recently established that L. donovani infection mediates macrophage polarization by broad range histone make over in polarized macrophages [34]. Our observations additionally highlight novel roles of super enhancers and epigenetic regulator protein BRD4 in sustained miR146a-5p expression during L. donovani infection which can be a promising juncture for transcriptional perturbation based therapeutics against VL.…”
supporting
confidence: 63%
“…Pharmacological inhibition of SMYD2 using AZ505 enhanced the protective inflammatory response in infected macrophage cell lines and decreased parasite multiplication in infected mice. Thus, SMYD2, along with other methyltransferases, aids Leishmania donovani in the process of infecting the host ( Parmar et al., 2020 ). Moreover, using human CD4+ cells lines and T cells from human immunodeficiency virus type 1 (HIV-1)-infected donors, Boehm et al.…”
Section: Host-pathogen Interactionsmentioning
confidence: 99%
“…Nonetheless, SMYD2 enzymatic activity is not restricted to H3K36, and this enzyme can also act on histone 4 lysine 20 (H4K20), among other targets ( Boehm et al., 2017 ; Yi et al., 2019 ). Through its methylatse activity, SMYD2 helps Leishmania donovani to infect the host organism ( Parmar et al., 2020 ) and activates HIV-1 latency ( Boehm et al., 2017 ). Furthermore, the majority of the data indicates that SMYD2 acts as an oncogene in blood malignancies, although there is some controversy.…”
Section: Conclusion and Further Directionsmentioning
confidence: 99%